The morphology and structural properties of silicon carbide quantum dots grown by very high frequency plasma enhanced chemical vapour deposition - Abd. Karim, Nur Farah Nadia (2019)
The growth and characterization of silicon carbide (SiC) quantum dots (QDs) are reported in this work. The SiC QDs were grown using plasma enhanced chemical vapour deposition (PECVD) at 150 MHz radio frequency (RF). A mixture of silane (SiH4) and methane (CH4) with a ratio of 1:4 and diluted in hydrogen (H2) was used as precursor gaseous. By manipulating the growth parameters such as hydrogen flow rate, growth temperature, growth time and RF power, the morphological and structural properties of SiC QDs were studied. The surface morphology of samples was observed through atomic force microscopy (AFM) and field emission scanning electron microscopy (FESEM). The structural properties of the sample were determined using Fourier transform infra-red (FTIR), emission dispersive x-ray (EDX) and Raman spectroscopy. It was found that a combination of dots formed islands on the substrate and the size of each dot was below 50 nm. By observing the cross-section view of the substrate, this self-assembled quantum dots followed Stranski-Krastanow (S-K) mode in which a combination of both islands and layer mode was formed. FTIR result showed absorption peaks located at 500 to 1000 cm-1 which proved the presence of SiC bonding. Further elemental mapping by EDX confirmed that the island and the layer underneath were formed from silicon, carbon and oxygen. This is in agreement with the observed SiC QDs cross-sectional FESEM image. The Raman spectra revealed three SiC polytypes which were 3C-SiC, 4H-SiC and 6H-SiC, and therefore in agreement with XRD results. All polytypes were considered as crystal due to small full width half maximum (FWHM) with crystallite size greater than 1 nm and sharp peaks were formed on Raman spectra. In conclusion, the SiC QDs growth parameters have shown a good impact to the morphological and structural properties of the grown quantum dots.